Molecular and clinical characterization of 25 individuals with exonic deletions of NRXN1 and comprehensive review of the literature123. Issue 4 (26th March 2013) - Béna, Frédérique; Bruno, Damien L.; Eriksson, Mats; van Ravenswaaij‐Arts, Conny; Stark, Zornitza; Dijkhuizen, Trijnie; Gerkes, Erica; Gimelli, Stefania; Ganesamoorthy, Devika; Thuresson, Ann Charlotte; Labalme, Audrey; Till, Marianne; et al.
Abstract This study aimed to elucidate the observed variable phenotypic expressivity associated with NRXN1 (Neurexin 1) haploinsufficiency by analyses of the largest cohort of patients with NRXN1 exonic deletions described to date and by comprehensively reviewing all comparable copy number variants in all disease cohorts that have been published in the peer reviewed literature (30 separate papers in all). Assessment of the clinical details in 25 previously undescribed individuals with NRXN1 exonic deletions demonstrated recurrent phenotypic features consisting of moderate to severe intellectual disability (91%), severe language delay (81%), autism spectrum disorder (65%), seizures (43%), and hypotonia (38%). These showed considerable overlap with previously reported NRXN1‐deletion associated phenotypes in terms of both spectrum and frequency. However, we did not find evidence for an association between deletions involving the β‐isoform of neurexin‐1 and increased head size, as was recently published in four cases with a deletion involving the C‐terminus of NRXN1. We identified additional rare copy number variants in 20% of cases. This study supports a pathogenic role for heterozygous exonic deletions of NRXN1 in neurodevelopmental disorders. The additional rare copy number variants identified may act as possible phenotypic modifiers as suggested in a recent digenic model of neurodevelopmental disorders. © 2013 Wiley Periodicals, Inc.